P PELANGGARAN HAKCIPTA BUKU: STUDI KASUS PENJUALAN BUKU BAJAKAN PADA FLATFORM ONLINE SHOP DI INDONESIA - Kinanti, Deneira Balqis; Rohmaniyah (Pustabiblia: Journal of Library and Information Science, 2024)
The sale of pirated books through online shop platforms in Indonesia has become a disturbing problem and threatens the integrity of copyright in this country. This article aims to investigate the phenomenon of copyright infringement in the context of selling pirated books on online shop platforms in Indonesia. Through an exploration of the sales methods used, their impact on the publishing industry and society, and countermeasures, this article provides an in-depth analysis of the problem. Literature studies and direct observations were carried out to understand the legal framework for copyright, the practice of book piracy on the internet, and the sale of pirated books in online shops. It was found that the sale of pirated books through online shop platforms resulted in financial losses for legitimate creators and publishers, as well as harming consumers by reducing the quality of the content. Apart from that, this phenomenon also hinders the growth of the publishing industry as a whole. Proposed countermeasures include strengthening the law, cooperation with online platforms, public awareness campaigns, increasing cooperation between parties, and empowering creators and publishers. By implementing these steps, it is hoped that the problem of copyright infringement in the sale of pirated books on online shop platforms in Indonesia can be addressed effectively, support the sustainable growth of the publishing industry, and protect the copyrights of creators and publishers.